1998
DOI: 10.1046/j.1468-2982.1998.1810690.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with aura: a review of 81 patients at 10-20 years' follow-up

Abstract: We investigated the evolution over time of migraine with aura (MA) in a number of MA patients consecutively referred to the University of Parma Headache Center in the period 1976-86. The follow-up period chosen for our review of the clinical condition of patients varied from a minimum of 10 years to a maximum of 20 years. The study group comprised 81 patients (55F, 26M), 21 of them (14.2%) with at least one parent with MA. Migraine without aura (MO) was also present in 29.6% of the patients studied. Currently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
6
21
0
3
Order By: Relevance
“…Of the 34 patients still having MA‐attacks, 27 patients experienced a headache during attacks (IHS 1.2) and 7 patients exclusively experienced aura without headache (IHS 1.2.5). Seven of the 27 patients who experienced a headache during MA‐attacks occasionally experienced migraine aura without headache (1.2.5). Of the 34 patients still having MA‐attacks 11 (32%) patients experienced migraine without aura at follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 34 patients still having MA‐attacks, 27 patients experienced a headache during attacks (IHS 1.2) and 7 patients exclusively experienced aura without headache (IHS 1.2.5). Seven of the 27 patients who experienced a headache during MA‐attacks occasionally experienced migraine aura without headache (1.2.5). Of the 34 patients still having MA‐attacks 11 (32%) patients experienced migraine without aura at follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…15,17,27 Predictive factors for worse prognosis of migraine are high migraine headache frequency, young age at onset, and overuse of medication. [3][4][5][6][7]14,22 The only known sources of information for the prognosis of tension-type headache are follow-up of cohorts with chronic daily headache, 28,29 child cohorts, 19,20,23,25 outpatients with tension-type headache, 30 juvenile outpatients, 10,11 and a case-control study of unspecified chronic daily headache. 31 No follow-up studies have been found for tension-type headache in adults from the general population.…”
mentioning
confidence: 99%
“…Types of migraine are not mutually exclusive and around 30% of people with migraine with aura also have attacks without aura,37 40 44 with the pattern changing over time. Women often experience a flurry of attacks of migraine with aura around puberty and then only have attacks without aura for many years.…”
Section: Diagnosing Migrainementioning
confidence: 99%
“…Women often experience a flurry of attacks of migraine with aura around puberty and then only have attacks without aura for many years. In later life, migraine aura without headache is more prevalent as headache becomes less of a feature with advancing age 40 44. Most people with attacks of migraine aura without headache have or have had migraine aura with headache 30 39…”
Section: Diagnosing Migrainementioning
confidence: 99%